Navigating the Complexities of Conscious Consumerism: The Moderating Effects of Age, Income, and Culture - Hussain, Sajid (Journal of Ecohumanism, 2025)
This paper investigates how environmental, ethical, social and personal factors impact conscious consumer choices while studying how age groups, income levels, cultural backgrounds and gender intersections influence these relationships. The study addresses a core problem in understanding which components drive sustainable purchasing behaviors among consumers because this understanding serves both companies and policymakers in their efforts for sustainable consumption.The findings of the study demonstrate that conscious consumerism receives substantial influence from ethical along with environmental considerations along with personal attributes and social factors. Through the research it became evident that age and income distributed the strength of relations between environmental and ethical elements and conscious consumer choices. The impact from gender together with cultural values showed smaller influences than other determinants of these relations. The results suggest ethical and environmental issues drive conscious consumerism more strongly than demographic factors such as age and income levels influence these behaviors. Creating effective conscious consumerism initiatives demands a comprehensive strategy which evaluates both customer belief systems and their social characteristics alongside their values.The findings demonstrates that understanding diverse elements shaping conscious consumerism remains vital along with analyzing demographic traits to explain consumer choices. The research delivers crucial findings which help businesses match their sustainability-based approaches to increasing customer demands while assisting governmental agencies in building sustainable consumption standards.